Secularism and its critics / edited by Rajeev Bhargava - "Bhargava, Rajeev (ed.)" (New Delhi, 1998)
his text puts together contemporary writings in the debate on secularism. It addresses urgent questions, including the relevance of secularism to non-Western societies, and the question of minority rights. Besides a theoretical section, a second section deals with secularism in America, Turkey and other countries. A third is on secularism in practice in India. The work should be of interest to scholars and students of political science, journalists, activists and all those interested in religion and politics and secularism.
Keywords: Secularism political aspects